Telomere Length Determination Based on Different Sex and Leaf Development of Snake Fruit (Salacca zalacca GART. VOSS.) Revealed by Polymerase Chain Reaction - Rima Indhirawati; Aziz Purwantoro (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2018)
Telomere has special roles at the ends of eukaryotic chromosomes that consisting of repeated DNA sequences. It protects chromosomes and DNA from damage. The plant sex and the leaf development may change in telomere length. Snake fruit (Salacca zalacca GART. VOSS.) is dioecious plants that have female and male organs on separate plants. The aim of this research is to determine the telomere length of snake fruit from different plant sex and the leaf development. In this research, we observed telomere length in snake fruit (female and male plants) using Polymerase Chain Reaction (PCR) procedure. The results from this study showed that telomere lengths of male and female are equal. Telomere lengths in the leaf development showed that younger leaves of both male and female leaves are longer compared to older and dried leaves.